Developing writing skills in English for specific purposes classrooms through literary texts - Shriganeshan, K. (THE JOURNAL OF TEACHING ENGLISH FOR SPECIFIC AND ACADEMIC PURPOSES, 2017)
With ten years of learning English as a second language at schools it has not become a reality for the university undergraduates in Sri Lanka that they become proficient in English. The exam-oriented studies of the present Sri Lankan educational system which was derived from the British colonial rulers encourages and also develops a textbook culture which would promote communication in English. In order to maintain international contacts, to use it in education, science, medicine, engineering, technology and business, and to lead a modern life, there was a need for Sri Lankans to study English. Therefore, experts of English language teaching have to find possible methods to teach it successfully in order to make the students perform their activities well in English. There was a time when it was felt that teaching of any language cannot be divorced from its literature. It is assumed that literature would arouse interest among the adult learners of English. The present study is to find out the possibilities of using literary texts to promote effective language learning at university level focusing on developing writing skills. The paper analyses how pieces taken from English literature and literature in English could be used in classrooms teaching English for Specific Purposes in order to motivate adult learners to become proficient in General English in the first phase. The study was conducted using questionnaires, interviews with the students, lecturers and administrators. Five workshop sessions were conducted at different intervals during the three-month study. The researcher was able to record the students’ involvement in the learning process from their written performance. The paper analyses and proves qualitatively how the students improved in their proficiency through teaching of literature.
Keywords: Culturally-friendly texts; Non-native English Literature; Syntactical; Linguistic features; Inter-disciplinary course